Pengaruh Social Media Marketing Brand Apparel Lokal Di Instagram Terhadap Purchase Intention Generasi Z Dengan Customer Trust Dan Perceived Value Sebagai Mediasi - Genacius Cokro, Jovan Audric; Kurniawati, Kurniawati (Fakultas Ekonomi Universitas Gresik, 2023)
This research is aimed to analyze the impact of social media marketing of Instagram on purchase intention with customer trust and perceived value as mediating variables within local apparel brand industry in Indonesia. This study used primary data in the form of questionnaires from 300 respondents which were distributed non-probabilistically to generation Z who are familiar with local apparel brands in the period October – November 2022. Hypothesis was analyzed with SEM-PLS method and the Baron and Kenny method using AMOS. Research finding shows that social media marketing has a positive effect on customer trust, perceived value, and purchase intention. Then, perceived value also has positive effect on purchase intention. However, customer trust does not have positive effect on purchase intention. In addition, customer trust and perceived value partially mediated the relationship from social media marketing to purchase intention